Method for extracting silicon resource by low-temperature smelting method and application thereof
Through the low-temperature alkaline smelting method and the use of surfactants, the problems of high preparation cost of silica aerogels and high energy consumption in the prior art are solved, and low-cost and high-performance silica aerosolization is achieved. Glue preparation, suitable for industrial applications.
Patent Information
- Application Number
- CN202411331338.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, the method for preparing silica aerogel has problems such as high cost, toxicity, high-temperature calcination, and long production cycle, which limits its industrial application.
Low-temperature alkaline smelting method is used, low-priced microsilicon powder is used as raw material, and the dispersion is enhanced by adding surfactant, and the preparation of high-performance silica aerogel is achieved under normal pressure drying conditions.
It realizes the preparation of high-performance silica aerogels at low cost and low temperature, reduces production costs, avoids energy consumption of high-temperature calcination, improves process safety, and increases the recycling rate of industrial solid waste.
Smart Images

Figure CN119143142A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inorganic oxide processing, and more specifically to a method for extracting silicon resources by a low-temperature smelting method and its application. Background Art
[0002] Aerogel is a solid material that is 99.8% air and is one of the lowest density solids in the world. The present invention involves silica aerogel, which has the advantages of low density, large specific surface area, and low thermal conductivity. This so-called "magic material that changes the world" has broad application prospects in the fields of aerospace, industrial insulation, and building materials. 2 Aerogels were first produced in the 1930s, but research progress was slow in the following decades. Later, it developed rapidly thanks to the revival of sol-gel technology. At present, silica aerogels are basically prepared by the sol-gel method. And in most cases, silicon alkoxides are selected as precursors, such as TEOS, TMOS, etc., and a three-dimensional network structure with mutual cross-linking is formed through the hydrolysis and polycondensation of silicon alkoxides. However, the selection of silicon alkoxides as precursors has problems such as high cost and drug toxicity, which is also one of the main reasons restricting the development of this industry. Using inorganic silicon sources as raw materials can overcome the shortcomings of high cost and toxicity of organic silicon sources to a certain extent.
[0003] SiO in industrial microsilica powder 2 It has an amorphous structure, with a content of up to 90%-95%, which is similar to crystalline SiO 2 Compared with SiO2, it has a higher chemical reactivity, and due to its small particle size and large surface area, it is easy to react with alkali to form water glass. Therefore, in theory, there is a way to prepare SiO2 with high porosity and high specific area. 2 The possibility of aerogel. Preparation of SiO using microsilica powder as raw material 2 Aerogel methods, such as patents CN110642257A and CN102795631A, both use microsilica powder and calcium oxide to calcine at a high temperature above 800°C, but still have problems such as high energy consumption, long production cycle, and high operating costs, and are not suitable for mass production and industrial applications.
[0004] Non-ionic surfactants can reduce the surface tension of water on the surface of silica, enhance the dispersibility of silica particles in water, and allow the alkali to more evenly contact the surface of silica particles, thereby accelerating the chemical reaction between silica and NaOH, speeding up the reaction process and shortening the reaction time, which can further reduce production costs.
[0005] Therefore, how to provide a method for preparing high-performance silica aerogel by low-temperature alkaline smelting is an urgent problem to be solved by those skilled in the art. Summary of the invention
[0006] In view of this, the present invention provides a method for extracting silicon resources by low-temperature smelting method and its application. The present invention uses low-priced and abundant microsilica powder as raw material, and adds a certain amount of surfactant to enhance the dispersibility of the raw material and improve the reaction activity. At the same time, the preparation of low-density and highly hydrophobic aerogel is achieved under normal pressure drying conditions.
[0007] One of the purposes of the present invention is to provide a method for extracting silicon resources by low temperature smelting, the specific steps of which are as follows:
[0008] S11. Mixing: Mix the silicon-containing raw material and the alkali in a certain proportion, add a certain amount of surfactant solution, and stir evenly;
[0009] S12. Melting: Melting the mixed product at low temperature, and crushing it after cooling;
[0010] S13. Dissolving: adding deionized water to the smelted product and dissolving in a water bath;
[0011] S14. Filtration: After dissolution is completed, separate the filtrate by filtration to obtain the water glass solution.
[0012] Preferably, in S11, the SiO 2 The content is above 80%, the mass ratio of the silicon raw material to the alkali is 1:1.0-1.8; the liquid-solid ratio of the surfactant solution to the silicon raw material and the alkali is 0.1-1.5 mL / g.
[0013] Further preferably, the silicon raw material is selected from any one or more of microsilica powder, coal gangue, and fly ash; the alkali is NaOH; and the surfactant includes but is not limited to anionic surfactants, cationic surfactants, zwitterionic surfactants, and nonionic surfactants.
[0014] Further preferably, the surfactant solution is an aqueous solution of polyoxyethylene alkyl ether.
[0015] Further preferably, the mass fraction of polyoxyethylene alkyl ether in the surfactant solution is 0.025%.
[0016] Preferably, in S12, the low-temperature smelting is at 300-550° C. and the smelting time is 10-90 min.
[0017] Preferably, in S13, the solid-liquid ratio of the smelting product to the deionized water is 1:2.5-5; and the water bath is 80-100° C. for dissolution for 50-70 min.
[0018] The second object of the present invention is a method for preparing high-performance silica aerogel, comprising the following steps:
[0019] S21. Preparing a water glass solution according to a method for extracting silicon resources by a low-temperature smelting method;
[0020] S22. First, dilute hydrochloric acid was added to adjust the pH value of the water glass solution, and the mixture was stirred thoroughly to form a uniform sol. Then, a sodium hydroxide solution was added to adjust the pH value of the sol, and the mixture was allowed to stand for more than 12 hours to obtain a gel.
[0021] S23. The gel was aged in a 55°C water bath for 12 to 24 h, crushed, and washed several times;
[0022] S24. collecting the filter residue by suction filtration, and immersing the filter residue in anhydrous ethanol for solvent exchange to obtain an alcohol gel;
[0023] S25. The alcohol gel is immersed in a mixed solution of trimethylchlorosilane and n-hexane for modification, and after the modification is completed, n-hexane is added for solvent exchange;
[0024] S26. Filter and collect the residue, and dry it at 80-150° C. under normal pressure for 4-7 hours to obtain high-performance silica aerogel.
[0025] Preferably, in step S22, the concentration of the dilute hydrochloric acid is 2-5 mol / L, and the pH is adjusted to 2-7; the concentration of the sodium hydroxide solution is 1-1.5 mol / L, and the pH is adjusted to 6-9.
[0026] Preferably, in S24, the solvent exchange is 10 to 14 hours.
[0027] Preferably, in S25, the volume ratio of the trimethylsilyl chloride to the n-hexane is 1:7-12, the modification time is 24 hours, and the solvent exchange time is 6-96 hours.
[0028] The third object of the present invention is to provide a high-performance silica aerogel, wherein the density of the silica aerogel is between 0.068 and 0.113 g / cm 3 The porosity is above 94.86%, and it has good thermal stability and performance within 400℃.
[0029] The technical concept of the present invention is: by using a surfactant to reduce the surface tension of water on the surface of silica, the dispersibility of silica particles in water is enhanced, so that the alkali can contact the surface of the silica particles more evenly, thereby accelerating the chemical reaction between silica and NaOH, speeding up the reaction process and shortening the reaction time, achieving the goal of preparing high-performance silica aerogel by low-temperature alkaline smelting, and further reducing production costs.
[0030] It can be seen from the above technical solution that, compared with the prior art, the beneficial effects of the present invention are:
[0031] (1) Low cost. The present invention uses industrial solid waste microsilica powder as raw materials, replacing expensive and toxic organic silicon sources. At the same time, it uses normal pressure drying instead of supercritical drying, which greatly reduces the requirements for equipment in the entire process, improves safety and reduces costs.
[0032] (2) Compared with the existing similar technologies, the present invention has made further improvements and upgrades. The sodium hydroxide particles with stronger alkalinity are selected. At the same time, a small amount of pure water is added to allow the raw materials to undergo sufficient contact reaction, without the need for high temperature above 800°C for calcination. Moreover, the small amount of water added will evaporate during the heating stage, which is fundamentally different from the wet preparation.
[0033] (3) Adding surfactants enhances the dispersibility of silica particles in water, making the contact between alkali and silica particles more uniform, thereby accelerating the reaction rate and degree of the two, which further reduces the reaction temperature and shortens the reaction time, greatly reducing the production cost.
[0034] (4) Increased the recycling rate of industrial solid waste and reduced environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0036] Figure 1 It is a curve diagram showing the relationship between the conversion rates of reaction materials with and without the addition of surfactant at different insulation temperatures.
[0037] Figure 2 It is a curve diagram showing the relationship between the conversion rates of the reaction materials with and without the addition of surfactant at different insulation times.
[0038] Figure 3 The SiO prepared in Example 1 2 TAG curve diagram of aerogel.
[0039] Figure 4 The figure is a curve diagram showing the relationship between the conversion rates when surfactant is added and when no surfactant is added under different alkali-ash ratios. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] (1) 5 g of microsilica powder and 7 g of sodium hydroxide particles were mixed evenly, and then 7.2 ml of deionized water was added and stirred to ensure that the two were fully in contact, and then calcined at 400° C. for 50 minutes.
[0043] (2) Add 60 ml of deionized water to the calcined product, filter after fully dissolving, and add 5 mol / L hydrochloric acid to the filtrate to adjust the pH value to 4. After sufficient stirring to form a uniform sol, add 0.5 mol / L sodium hydroxide solution to adjust the pH value to 7, and let it stand for twelve hours to gel.
[0044] (3) Place the fresh gel in a 55°C water bath for aging for 24 hours.
[0045] (4) After aging, the wet gel was broken and washed with deionized water for three times.
[0046] (5) Filter by suction, and immerse the filter residue in anhydrous ethanol for 12 hours to perform solvent exchange.
[0047] (6) Then added into a mixed solution of n-hexane and trimethylsilyl chloride for modification (V TMCS :V 正己烷 =1:9), and after the modification was completed, the solvent was exchanged again with n-hexane.
[0048] (7) After filtration, the residue was dried at 80°C for 2 hours and then heated to 100°C and maintained for 3 hours.
[0049] Example 2
[0050] The step (1) in Example 1 is replaced by "mix 5 g of microsilica powder and 7 g of sodium hydroxide particles evenly, then add 7.2 ml of deionized water with a surfactant added thereto, and stir to ensure full contact, wherein the surfactant is added in an amount of 0.025% in water. Then calcine at 400°C for 50 minutes", and the rest is the same as in Example 1.
[0051] Example 3
[0052] The step (1) in Example 1 is replaced by “mix 5 g of microsilica powder and 7 g of sodium hydroxide particles evenly, and then calcine at 400° C. for 50 minutes”, and the rest is the same as Example 1.
[0053] Example 4
[0054] The step (1) in Example 1 is replaced by "mix 5 g of microsilica powder and 7 g of sodium hydroxide particles evenly, then add 4 ml of deionized water with a surfactant added thereto, and stir to ensure full contact, wherein the surfactant is added in an amount of 0.025% in water. Then calcine at 400°C for 50 minutes", and the rest is the same as Example 1.
[0055] Example 5
[0056] The step (1) in Example 1 is replaced by “mix 5 g of microsilica powder and 5 g of sodium hydroxide particles evenly, then add 6.3 ml of deionized water to which a surfactant is added and stir to ensure full contact, wherein the ratio of the surfactant added to the water is 0.025%. Then calcine at 400°C for 50 minutes”, and the rest is the same as Example 1.
[0057] Example 6
[0058] The step (1) in Example 1 is replaced by “mix 5 g of microsilica powder and 6 g of sodium hydroxide particles evenly, then add 6.9 ml of deionized water to which a surfactant is added and stir to ensure full contact, wherein the ratio of the surfactant added to the water is 0.025%. Then calcine at 400°C for 50 minutes”, and the rest is the same as Example 1.
[0059] Example 7
[0060] The step (1) in Example 1 is replaced by “mix 5 g of microsilica powder and 8 g of sodium hydroxide particles evenly, then add 8.1 ml of deionized water to which a surfactant is added and stir to ensure full contact, wherein the ratio of the surfactant added to the water is 0.025%. Then calcine at 400°C for 50 minutes”, and the rest is the same as Example 1.
[0061] Example 8
[0062] The step (1) in Example 1 is replaced by “mix 5 g of microsilica powder and 9 g of sodium hydroxide particles evenly, then add 8.7 ml of deionized water to which a surfactant is added and stir to ensure full contact, wherein the ratio of the surfactant added to the water is 0.025%. Then calcine at 400°C for 50 minutes”, and the rest is the same as Example 1.
[0063] For the aerogel product prepared in the above embodiment, the density and porosity were measured using a Lichen solid density meter (XF-200S), and the results are shown in Table 1:
[0064] Table 1SiO 2 Density and porosity of aerogels
[0065]
[0066]
[0067] As can be seen from Table 1, in the present invention, by optimizing the mixing and melting conditions, the density and porosity of the aerogel can be significantly affected.
[0068] Figure 1 and Figure 2 The following are the relationship curves of the conversion rates corresponding to the case where a surfactant is added (Example 2) and the case where no surfactant is added (Example 1) at different insulation temperatures and insulation times:
[0069] As can be seen from the above figure, the addition of surfactants significantly improves the conversion rate. Without the addition of surfactants, the curve change from 300°C to 350°C is the most obvious, which may be due to the fact that the melting point of sodium hydroxide has not been reached at 300°C and the contact of the reaction materials is not sufficient. After adding the surfactant, the conversion rate has been significantly improved, which also proves that the surfactant makes the contact between the alkali and the silica particles more uniform, thereby increasing the reaction rate and degree of the two, thereby reducing the time required for the entire reaction and reducing production costs.
[0070] The thermal stability of the aerogel product prepared in Example 1 was analyzed using a thermogravimetric reaction system. The results are as follows: Figure 3 As shown:
[0071] Depend on Figure 3 It can be seen that when the temperature reaches above 400 °C, the -CH 3 The groups become unstable and begin to decompose, which will cause the hydrophobic properties of the aerogel to decrease. Therefore, within 400°C, the product has good thermal stability and performance.
[0072] Figure 4 The graph shows the relationship between the conversion rate with and without surfactant added at different alkali-ash ratios. When the alkali content is less than 1.5, the conversion rate increases sharply with the increase of alkali content, and then the growth trend slows down; at the same time, after adding surfactants, the conversion rate has an overall improvement, especially in the low alkali-ash ratio stage, the improvement effect is more obvious.
[0073] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for extracting silicon resources by low temperature smelting method, It is characterized in that The following steps are involved: S11. Mixing: Mix the silicon-containing raw material and the alkali in a certain proportion, add a certain amount of surfactant solution, and stir evenly; S12. Melting: Melting the mixed product at low temperature, and crushing it after cooling; S13. Dissolving: adding deionized water to the smelted product and dissolving in a water bath; S14. Filtration: After dissolution is completed, separate the filtrate by filtration to obtain the water glass solution.
2. A method for extracting silicon resources by low-temperature smelting according to claim 1, It is characterized in that In S11, SiO in the silicon raw material 2 The content is more than 80%, and the mass ratio of the silicon raw material to the alkali is 1:1.0-1.8; The liquid-to-solid ratio of the surfactant solution to the silicon raw material and the alkali is 0.1 to 1.5 mL / g.
3. A method for extracting silicon resources by low-temperature smelting according to claim 2, It is characterized in that The silicon raw material includes any one or more of microsilica powder, coal gangue, and fly ash; the alkali is NaOH; and the surfactant includes but is not limited to anionic surfactants, cationic surfactants, zwitterionic surfactants, and nonionic surfactants.
4. A method for extracting silicon resources by low-temperature smelting according to claim 1, It is characterized in that In S12, the low-temperature smelting is at 300-550° C. and the smelting time is 10-90 minutes.
5. A method for extracting silicon resources by low temperature smelting method according to claim 1, It is characterized in that In S13, the solid-liquid ratio of the smelting product to the deionized water is 1:2.5-5; the water bath is 80-100° C. for dissolution for 50-70 min.
6. Application of a low-temperature smelting method to extract silicon resources, It is characterized in that The following steps are involved: S21. Preparing a water glass solution according to any one of claims 1 to 5; S22. First, dilute hydrochloric acid was added to adjust the pH value of the water glass solution, and the mixture was stirred thoroughly to form a uniform sol. Then, a sodium hydroxide solution was added to adjust the pH value of the sol, and the mixture was allowed to stand for more than 12 hours to obtain a gel. S23. The gel was aged in a 55°C water bath for 12 to 24 h, crushed, and washed several times; S24. collecting the filter residue by suction filtration, and immersing the filter residue in anhydrous ethanol for solvent exchange to obtain an alcohol gel; S25. The alcohol gel is immersed in a mixed solution of trimethylchlorosilane and n-hexane for modification, and after the modification is completed, n-hexane is added for solvent exchange; S26. Filter and collect the residue, and dry it at 80-150° C. under normal pressure for 4-7 hours to obtain high-performance silica aerogel.
7. Application of the low temperature smelting method for extracting silicon resources according to claim 6, It is characterized in that In step S22, the concentration of the dilute hydrochloric acid is 2-5 mol / L, and the pH is adjusted to 2-7; the concentration of the sodium hydroxide solution is 1-1.5 mol / L, and the pH is adjusted to 6-9.
8. Application of the low temperature smelting method for extracting silicon resources according to claim 6, It is characterized in that In S24, the solvent exchange is 10 to 14 hours.
9. Application of the low-temperature smelting method for extracting silicon resources according to claim 6, It is characterized in that In S25, the volume ratio of the trimethylsilyl chloride to the n-hexane is 1:7-12, the modification time is 24 hours, and the solvent exchange time is 6-96 hours.
Citation Information
Patent Citations
Method for preparing silicon dioxide aerogel
CN102795631A
Method for preparing silicon dioxide aerogel by using silicon micropowder
CN110642257A
